Engineering TiO2/Perovskite Planar Heterojunction for Hysteresis‐Less Solar Cells. Issue 22 (26th September 2016) - Trifiletti, Vanira; Manfredi, Norberto; Listorti, Andrea; Altamura, Davide; Giannini, Cinzia; Colella, Silvia; Gigli, Giuseppe; Rizzo, Aurora
Abstract : Hybrid halide perovskite solar cells generally show differences in the power output depending on the voltage sweep direction, an undesired phenomenon termed hysteresis. Although the causes of this behavior have not yet been univocally determined, commonly, hysteresis heavily affects solar cells based on flat TiO2 as electron extracting layer. Herein, it is shown how perovskite material quality has a preeminent impact on hysteresis, and how combined deposition and post‐deposition engineered manufacturing could lead to highly efficient and hysteresis‐less solar cells, notwithstanding a planar TiO2 ‐based layout. This methodology relies on solvent engineering during the casting process, leading to an ultra‐flat, uniform, and thick film ensuring an optimal interface connection with the charge‐extracting layer combined with post‐deposition thermal and vacuum treatments, which merge the crystalline domains and cure the defects at the grain boundaries. This method allows obtaining perovskite active layer with superior optical properties, explaining the ideal device behavior and performances, therefore, a simple optimization of perovskite processing conditions can efficiently stem hysteresis targeting different device layouts. Power conversion efficiency of 15.4% and reduced hysteresis are achieved. Abstract : Perovskite material quality has a preeminent impact on hysteresis . The presented method relies on solvent engineering during the casting process, leading to a thick film that ensures an optimal interface connection with the charge‐extracting layer. This method allows obtaining perovskite active layer with superior optical properties, explaining the ideal device behavior and device performances.